RISK FACTORS OF LOW BIRTH WEIGHT (LBW) AND PRETERM DELIVERY ASSOCIATED WITH THE INCIDENCE OF NEONATAL ASPHYXIA : A CROSS SECTIONAL STUDY - Dwi Saputri Mayang Sari; Desti Widya Astuti; Viony Anatila Valentin Nadya (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Neonatory asphyxia is the inability to breathe spontaneously and irregularly at birth or shortly after birth. The purpose of this study was to determine the relationship between LBW and preterm labor with the incidence of neonatal asphyxia in the neonatal ward of the Regional General Hospital (RSUD) of Prabumulih. This study used an analytical survey with a cross-sectional approach. The population of thNeonatory asphyxia is the inability to breathe spontaneously and irregularly at birth or shortly after birth. The purpose of this study was to determine the relationship between LBW and preterm labor with the incidence of neonatal asphyxia in the neonatal ward of the Regional General Hospital (RSUD) of Prabumulih. This study used an analytical survey with a cross-sectional approach. The population of this study was all infants born at Prabumulih City Hospital between January and December 2024. A random sampling technique was used to select 256 newborns. The research instrument was a checklist. The bivariate analysis showed a significant association between low-birth-weight (LBW) and neonatal asphyxia (p-value 0.000). Preterm birth was significantly associated with neonatal asphyxia (p-0.000). The conclusion of this study is that there is a significant relationship between low birth weight (LBW) and preterm birth and the incidence of neonatal asphyxia in the neonatal ward of Prabumulih.is study was all infants born at Prabumulih City Hospital between January and December 2024. A random sampling technique was used to select 256 newborns. The research instrument was a checklist. The bivariate analysis showed a significant association between low-birth-weight (LBW) and neonatal asphyxia (p-value 0.000). Preterm birth was significantly associated with neonatal asphyxia (p-0.000). The conclusion of this study is that there is a significant relationship between low birth weight (LBW) and preterm birth and the incidence of neonatal asphyxia in the neonatal ward of Prabumulih.